Trade reform, managers, and skill intensity: Evidence from India - Pavel Chakraborty (Asian Development Bank Institute (ADBI), 2019)
India underwent a significant structural transformation through trade liberalization and other reforms (domestic) in the 1990s because of a balance-of-payments crisis. I use this episode to identify the causal effect of a drop in tariffs on wage inequality, measured through managerial and nonmanagerial compensation, between 1990 and 2011. I find that a drop in input tariffs (and not output) significantly increases the share of managerial compensation. In other words, a decline in tariffs on intermediate inputs raised within-firm wage inequality. A 10% drop in tariffs increases the managerial compensation by 0.5%-3.5%. Additionally, I find that this increase in the compensation for managers (or observed increase in wage inequality) can possibly be explained by the rise in skill intensity, but only for firms below halfway in the size distribution. On the other hand, I do not find any evidence of a demand shift from nonmanagers due to a drop in tariffs, leading to inconclusive evidence in favor of skill premium. Additional analysis reveals that it is also the drop in the supply of skilled labor, coupled with demand shifts (toward managerial workers), that led to the rise in the demand for skill for certain categories of workers.
Keywords: F1; F66; F14; M12; 330; trade liberalization; input tariffs; demand for managers; small and medium-sized firms; skill intensity